Insurance Instability and Its Impact on Care of Young Adult Survivors of Pediatric Cancer: A Project Forward Study. (20th August 2020) - Mobley, E.; Cousineau, M.; Kim, S.; Miller, K.; Tobin, J.; Freyer, D.; Milam, J.
Abstract : By 2020, there will be more than 500, 000 childhood cancer survivors (CCS) in the United States. CCS experience disparities in economic, social, and health‐related quality of life outcomes, and these disparities are magnified for CCS who are uninsured. Access to long‐term follow‐up (LTFU) care for surveillance, preventive care, and treatment of late effects for survivors are vital to improve long‐term outcomes. Inadequate insurance coverage, high out‐of‐pocket costs, and lack of perceived need for care have been shown to affect access to LTFU care among CCS. The objectives of this study were to (1) assess insurance instability longitudinally and describe patient factors that correlate with instability and (2) examine whether insurance instability and financial or patient factors influence access to LTFU care. Project Forward was a population‐based, observational study of CCS in Los Angeles County using California Cancer Registry (CCR) data to identify participants who completed a survey. Change in insurance coverage was assessed at diagnosis using CCR data and at survey and its impact on LTFU care. Those who experienced any change in insurance coverage ("insurance instability") were set equal to one. Multivariable logistic regression models incorporating survey nonresponse weights were used to estimate the change in the marginal predicted probabilities of insurance instability and LTFU care, adjusted for demographic, socioeconomic, and clinical covariates and clustered by treating hospital. Study participants were diagnosed with cancer between the ages of 0 and 19 while living in Los Angeles County between 1996 and 2010 and were older than 21 at the time of survey, from 2015 to 2017 (N = 1106). Almost half (48%; N = 529) of participants experienced insurance instability from diagnosis to survivorship, while 577 did not. After adjusting for demographic, socioeconomic, and clinical covariates, the multivariable model predicting insurance instability indicated that being uninsured at diagnosis or at survey increased the probability of instability by 37% ( P < .001) and 58% ( P < .001), respectively, in comparison with those with private insurance. The multivariable model predicting LTFU care indicated that those who experienced insurance instability decreased the probability of LTFU care by 5% ( P < .05), in comparison with those who did not experience instability. When compared to those with private insurance coverage at diagnosis, participants who were covered by Medicaid, Medicare, or Indian Health Service plans at diagnosis were more likely to participate in LTFU care by 5% ( P < .05); however, those who were uninsured at the time of the survey were less likely to participate in LTFU care by 10% ( P < .05). CCS who were uninsured at diagnosis or survivorship were more likely to experience insurance instability. Insurance instability and being uninsured during survivorship were negatively associated with access to LTFU care; however, those with public insurance coverage at diagnosis were positively associated with access to LTFU care. Reducing insurance instability for CCS will improve access to LTFU care. This insight is key to improving health, reducing unnecessary and inappropriate health care use, and decreasing costs, while promoting services that can preserve and improve health for CCS. The study was funded by the National Institutes of Health.